Odpowiedzi

2009-11-22T19:02:50+01:00
[(1-0,7)do potengi 2+3i jedna trzecia*1,2]*100-406=
[(1-0,7)²+3⅓*1,2]*100-406= [(0,3)²+ 4] * 100 - 406 = 4,09 * 100 - 406 = 3
2009-11-22T19:04:54+01:00
[(1-0,7)do potengi 2+3i jedna trzecia*1,2]*100-406=
= [ (0,3)² + 3⅓ *12/10] *100 -406 =
= [ 0,09 + (10/3)*(6/5)]*100 -406=
= [ 0,09 + 4] *100 -406=
= 4,09*100 - 406 =
= 409 -406 = 3

2009-11-22T19:05:46+01:00
[(1-0,7)²+3⅓*1,2]*100-406=[(0,3)²+3⅓*12/10]*100-406=
=[0,09+10/3*12/10]*100-406= [0,09+4]*100-406= 4,09*100-406=409-406=3